2021
DOI: 10.2174/1871530320999201209222921
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Teplizumab for Treatment of Type One Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Background:: Type one diabetes mellitus (T1DM) is an autoimmune disease characterized by gradual destruction of beta cells in islets of Langerhans. Teplizumab is a humanized anti-CD3 monoclonal antibody, which may have beneficial effects for T1DM patients. Objective:: To assess the safety and efficacy of teplizumab in T1DM patients. Methods:: We searched electronic databases using related keywords for randomized clinical trials that assessing the safety and efficacy of teplizumab. We evaluated the retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
2
14
2
Order By: Relevance
“…Another study by Nourelden et al 33 assessed the efficacy of teplizumab as a treatment for T1DM. Their study included a systematic review of relevant articles, analysed using a review manager.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Nourelden et al 33 assessed the efficacy of teplizumab as a treatment for T1DM. Their study included a systematic review of relevant articles, analysed using a review manager.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical trials of peptide immunotherapy found that 10 μg C19-A3 proinsulin peptide s.c. every 2 weeks was well tolerated in patients with recent-onset T1D ( 31 ), while 60–150 μg weekly s.c. administration of celiac disease–relevant peptides induced dose-dependent gastrointestinal symptoms associated with T cell IL-2 production ( 32 34 ). Similarly, proinflammatory adverse effects of anti-CD3 immunotherapy in T1D were dose dependent ( 35 ). Taken together, we hypothesize that transient increases in joint symptoms after a 3 mL dose correspond to the strength of TCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…8 The reliability and validity of these results were corroborated by data from a meta-analysis of eight randomised controlled trials with 866 patients designed to assess the efficacy of teplizumab. 14 This found teplizumab was associated with lower insulin use than placebo at 6, 12, 18 and 24 months and improved β-cell function and insulin production. No significant effect of teplizumab on HbA1c levels was observed at any time point.…”
Section: Teplizumab: Clinical Effectivenessmentioning
confidence: 93%